I, Ripper - Hunter, Stephen 1946-; Page, Michael (Michael J.); Page, Jane Z.; Dreese, Lee; Brilliance Audio (Firm) (Grand Haven, Michigan : Brilliance Audio, 2015)
Takes you deep inside the mind of the most notorious serial killer of all time: Jack the Ripper. In the fall of 1888, Jack the Ripper slaughtered five prostitutes in London's seamy Whitechapel District. He did not just kill-he ripped with a butcher's glee-and then, after the particularly gruesome slaying of Mary Jane Kelly, he disappeared. For 127 years, Jack has haunted the dark corners of our imagination, the paradigm of the psychotic killer.
Keywords: Jack, -- the Ripper -- Fiction; Serial murderers -- Fiction -- England; Audiobooks; London (England) -- Fiction -- History -- 19th century; Whitechapel (London, England) -- Fiction; Suspense fiction; Mystery fiction; Audiobooks